Vocalic Intrusions in Consonant Clusters in Child-Directed vs. Adult-Directed Speech - Garmann, Nina Gram; Hansen, Pernille; Simonsen, Hanne Gram; Holm, Elisabeth; Tengesdal, Eirik; Post, Brechtje; Payne, Elinor (Frontiers in Psychology, 2021)
In this paper, we investigate a prosodic-phonetic feature in child directed speech within a dynamic, complex, interactive theoretical framework. We focus on vocalic intrusions, commonly occurring in Norwegian word initial consonant clusters. We analysed child-directed speech from nine Norwegian-speaking mothers to their children, aged 2;6, 4, and 6 years, and compared the incidence and duration of vocalic intrusions in initial consonant clusters in these data with those in adult-directed speech and child speech. When viewed overall, vocalic intrusion was found to be similar in incidence in child- and adult-directed speech. However, closer examination revealed differential behaviour in child-directed speech for certain conditions. Firstly, a difference emerged for one particular phonetic context: While vocalic intrusions in /Cr/ clusters are frequent in adult-directed speech, their presence is near-categorical in child-directed speech. Secondly, we found that the duration of vocalic intrusions was longer in child- than in adult-directed speech, but only when directed to 2;6-year-olds. We argue that vocalic intrusions in child-directed speech may have both a bonding as well as a didactic function, and that these may vary according to the age of the child being addressed.